Frequency of Number of Dialysis Done in Patients with CKD and then Compare the Frequency of HCV Infection in Patients with CKD on Hemodialysis - Muhammad Yasir Younis, Saad Hassan Khan, Soniasaleem, Muhammad Azhar Waseem, Asmat Ullah, Sadia Jabbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of number of dialysis done in patients with CKD and then compare the frequency of HCV infection in patients with CKD on hemodialysis Study Design: Cross sectional study Setting: Medical Unit I, Department of Gastroenterology, Lahore General Hospital, Lahore. Duration: The study was conducted for a period of six months from 15th December, 2017 to 18th June, 2018. Methodology: A total of 120 patients were included in the study. Then number of dialysis done was also noted. Blood sample was sent to the pathology laboratory and HCV was labeled. All the data was recorded on proforma. Data was analyzed with IBM-SPSS version 21. Results: In this study, the mean age of patients was 47.47±18.65years. There were 56 (46.7%) male while 64 (53.3%) female patients. The mean BMI of patients was 22.62±4.04kg/m2. In this study, 57 (47.5%) had <50 dialysis sessions, 40 (33.3%) had 50-100 sessions, 14 (11.67%) had 101-200 sessions and 9 (7.5%) had >200 sessions. In patients with <50 dialysis, 10 (17.5%) had HCV, patients with 50-100 dialysis, 9 (22.5%) had HCV, patients with 100-200 dialysis, 7 (50%) had HCV and patients with>200 dialysis, 5 (55.6%) had HCV. The difference was significant (p<0.05). Conclusion: The frequency of HCV was significantly higher in patients with >100 sessions of dialysis as compared to <100 dialysis sessions.